Diagnostic concordance between skeletal cephalometrics, radiograph-based soft-tissue cephalometrics, and photograph-based soft-tissue cephalometrics. (8th December 2016) - Nucera, Riccardo; Lo Giudice, Antonino; Bellocchio, Mirea; Spinuzza, Paola; Caprioglio, Alberto; Cordasco, Giancarlo
Summary: Objective: This study aims to investigate the diagnostic concordance between skeletal cephalometrics and soft-tissue cephalometrics in identifying facial lower third characteristics. Materials and methods: We compared a skeletal cephalometric analysis (SCA) to a soft-tissue analysis performed on cephalometric radiographs (rSTCA) and to one performed on profile photograph (pSTCA). Ninety-six pre-treatment digital lateral cephalometric radiographs and 96 digital profile photographs were randomly selected for this study (patients' mean age: 18.33, SD: 3.38, age range: 14–29). Inclusion criteria were as follows: no skeletal asymmetry, well-aligned upper and lower dental arches, no history of orthodontic treatment, prosthodontic treatment, facial surgery and trauma, patient's age between 14 and 30 years, high-resolution images, exams taken with natural head position. Kruskas–Wallis and post hoc pairwise comparisons tests were used to find differences among the considered cephalometric methods. The diagnostic performance of the three methods was also assessed using the receiver-operating characteristic (ROC) curve analysis. Results: Significant differences were found between SCA and rSTCA and between SCA and pSTCA in defining sagittal and vertical facial lower third characteristics ( P < 0.05). No differences were found between rSTCA and pSTCA ( P > 0.05) for the same facial characteristics. For each parameters investigated, pSTCA showed an area under the curve much closer to the perfect value of 1.00. Conclusion: Poor diagnostic concordance was found between SCA and rSTCA and between SCA and pSTCA. pSTCA is a reliable method for evaluating the soft-tissue profile characteristics compared to that performed on cephalograms.